THE TEST OF MINIMUM NUMERACY COMPETENCY FOR LEVEL 2 USING AN ONLINE QUIZIZZ PLATFORM: INSTRUMENT DEVELOPMENT - Islam, Fahrul; Syahrul, Syahrul; Patahuddin, Patahuddin (Universitas Labuhanbatu, 2025)
Purpose – This study aims to develop and test the reliability of the Level 2 Numeracy AKM instrument presented through an online quiz platform. The development of this instrument aims to address the need for a practical, easily accessible digital assessment tool that can enhance student engagement, particularly in efforts to strengthen the numeracy skills of elementary school students in Indonesia.Methodology - This study employs a Research and Development (R&D) approach, adapting the ADDIE model and Retnawati's instrument development framework (analysis, design, development, user trials, and evaluation). The instrument, comprising 20 items, was designed to cover key numeracy indicators. Data were collected from 38 fourth-grade students across four elementary schools and two expert validators. The analysis included content validity assessment using Gregory's model, media feasibility analysis, reliability testing with McDonald’s Omega, and a descriptive analysis of student performance and feedback.Findings – The research confirmed the high quality of the developed instrument. The developed instrument demonstrates very high content validity, as indicated by a Cronbach's alpha coefficient of 1.00 and an average validator rating of 3.45 on a scale of 4. Its reliability level is also strong, as evidenced by a McDonald's Omega value of 0.81, reflecting good internal consistency. Student responses were also very positive. The practicality score indicating that the instrument is considered engaging, easy to use, and convenient to access. In the field trial, students were able to solve fundamental problems. However, most still had difficulties when dealing with more complex material, especially fraction comparisons and algebraic concepts.Contribution –Overall, this study makes an important contribution in the form of a practical and validated model for developing digital-based numeracy assessment instruments that align with national AKM standards and international evaluation frameworks, such as PISA.